Organized Crime In The Balkans - Krasniqi, Kole (European Scientific Journal, ESJ, 2016)
Legal systems are put in jeopardy and social stability and welfare are harmed wherever there are organized criminal activities. In the Balkans, organized crime is also tantamount to a main obstacle to the European integration of the region. The permanent influence of organized crime on the state structures, the cooperation between different criminal organizations and especially their collaboration with some extremist groups impact political stability in an extremely negative way. The states in the Balkans have recognized the dangers for their peoples constituted by organized crime and have already taken a number of required legal, institutional and political measures in order to be able to successfully combat organized crime. However, organized crime still constitutes the main risk to the new democratic states in the Balkans in spite of these measures. For that reason, combating organized crime may not treated just as the task or responsibility of one single state but it needs to be understood as an obligation and responsibility of all the states in the entire region as well as of the European Union. Therefore, cooperation and coordination of joint activities for combating organized crime have to be based on modern international standards. Besides, a continual perspective is required according to the interest of the peoples of the region to live together in peace and mutual harmony and to establish a society where human rights are not threatened by criminal violence but protected just like in the European Union.